Efektivitas Biro Umum dalam Menjalankan Program E-Surat di Sekretariat Daerah Provinsi Kalimantan Barat - Rizky Permata Sari (JPASDEV : Journal of Public Administration and Sociology of Development, 2021)
The purpose of this research was to find out and analyze the effectiveness of the bureau of general affairs in running the Electronic Letter program at The Regional Secretariat of West Kalimantan Province. This Study uses Gibson et al’s theory of short-term Effectiveness which is seen from production, effieciency, and satisfaction. The method used in this research is qualitative, with descriptive research. The results showed that the effectiveness of bureau of general affairs in running the Electronic Letter program at The Regional Secretariat of West Kalimantan Province already existed but was not optimal. The effectiveness of the bureau of general affairs in running the Electronic Letter program has not been effective, due to, namely a) production; which consists of incoming letter service, mail disposition information services, letter numbering service have been running according to the stages even more efficient when viewed from the previous system, but not yet optimal. This is evidenced by the internet network that is still experience problems, employees or admins who are still experiening human error, and limited facilities and infrastructure; b) effieciency; which consists of time efficiency, service cost efficiency and service procedure effieciency, in terms of efficiency both internal and external parties state that it is quite optimal because the service is faster and more efficient but still needs to be improved; c) satisfaction; internal parties feel they are quite satisfied even though they are not optimal because there are still problems in the production section, but external parties are not satisfied this is because there are parties who are still having trouble tracking the whereabouts of the letter. The recommendations of this research are: 1) changing the mindset of employees gradually by increasing socialization related to the Electronic Letter program and increasing the motivation of each employee by building good relations between employees within the The Regional Secretariat of West Kalimantan Province; 2) involving all OPD (regional device organizations) to use the Electronic Letter application; 3) the provision of good facilities and infrastructure. Keywords: Effectiveness, The Electronic Letter Program, Bureau of General Affairs